Thresh / hold - Brown, Rachel Linnea, author; Beachy-Quick, Dan, advisor; Steensen, Sasha, committee member; Fiege, Mark, committee member (Colorado State University. Libraries, 2014)
Thresh / Hold, largely autobiographical, embodies the emotional fracture of leaving my childhood home, but ultimately progresses toward acceptance of a present self. In other words, I seek what "I can assemble / whole" via poems. Such mending necessitates exploring memory as a means of both preservation and declaration—Here is what I was, I know who I am. While only "Mystic" specifically addresses ancestry in Thresh / Hold, familial sensibilities inform my entire thesis—after all, looking back exposes layers of meaning. This depth (artifacts or truths revealed if one only digs in the right places or uses the right diction) yields tunnels hidden within tunnels, photographs under paintings, bewildering holes, and newfound windows. I thus privilege objects seen vividly and thoughts felt profoundly, capturing the essence and emotional impact of beloved beings and scenes. Simple images recur, including familiar trees (oak, pine, maple, or sycamore) and stars, which are so bright and spangled at home. These repeated images capture both what is and was while also recognizing life's inherent changes. Damages or fractures—losses—do not always debilitate, as Thresh / Hold concludes. Clocks turn on—that is normal—and fine.